OPTIMALISASI SISTEM PENGOPERASIAN GENERATOR SET MENGGUNAKAN METODE LAGRANGE - Dulhadi, Dulhadi; Suyanta; Pramudita, Eufrasia Andranetta Gracelynne Eka; Afifudin, Shodiq; Putri, Dewi Indriati Hadi; Pratama, Hafiyyan Putra (KURVATEK, 2025)
Yogyakarta International Airport has high power demands, supplied by GI Wates with a subscribed capacity of 2 × 8.66 MVA and five generator sets (gensets) each with a capacity of 2.5 MVA. Due to fluctuating flight schedules, all gensets operate simultaneously, leading to inefficient fuel consumption. This study aims to optimize the genset operation pattern using the Lagrange method based on historical energy and fuel consumption trends. The results show that only genset 1 operates optimally (83.26%) under normal conditions. In the event of a genset failure, the load is redistributed to other gensets with lower output to maintain efficiency and reliability. This approach increases efficiency, reduces fuel consumption, and extends engine lifespan. The optimization supports more energy-efficient and reliable airport operations.